Casein Kinase 1 Family Member CK1δ/Hrr25 Is Required for Autophagosome Completion - Li, Yuting; Chen, Xuechai; Xiong, Qianqian; Chen, Yong; Zhao, Hongyu; Tahir, Muhammad; Song, Jingdong; Zhou, Bing; Wang, Juan (Frontiers in Cell and Developmental Biology, 2020)
Autophagy starts with the initiation and nucleation of isolation membranes, which further expand and seal to form autophagosomes. The regulation of isolation membrane closure remains poorly understood. CK1δ is a member of the casein kinase I family of serine/threonine specific kinases. Although CK1δ is reported to be involved in various cellular processes, the role of CK1δ in autophagy is unknown. Here, we show that CK1δ regulates the progression of autophagy from the formation of isolation membranes to autophagosome closure, and is essential for macroautophagy. CK1δ depletion results in impaired autophagy flux and the accumulation of unsealed isolation membranes. The association of LC3 with ATG9A, ATG14L, and ATG16L1 was found to be increased in CK1δ-depleted cells. The role of CK1δ in autophagosome completion appears to be conserved between yeasts and humans. Our data reveal a key role for CK1δ/Hrr25 in autophagosome completion.